Results 1 to 3 of 3

Math Help - Solving Diff Eq with initial conditions and first 6 coefficients...

  1. #1
    Newbie
    Joined
    Mar 2013
    From
    Kansas
    Posts
    1

    Solving Diff Eq with initial conditions and first 6 coefficients...

    I need some help here because I am completely lost!!!

    I need to solve the ODE (1-x)y''-y'+xy=0 using the initial conditions of y(0)=1, y'(0)=1.

    So far I have (1-x)y''-y'=-xy and (1-x)y''=-xy+y' but this is where I got lost. I know it's something really simple but I still can't seem to find the error and I don't know where to go next!!!

    I have to find the general pattern and show my final answer is equal to y=e^x...

    Thanks for the help!!!!!!!
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor

    Joined
    Apr 2005
    Posts
    16,004
    Thanks
    1659

    Re: Solving Diff Eq with initial conditions and first 6 coefficients...

    Your title says "first six coefficients". Coefficients of what? I suspect you were expected to find a power series sollution.
    There are two ways you can do that:
    1) Write the solution as a power series: y= \sum_{n=0}^\infty a_nx^n so the y'= \sum_{n=0}^\infty na_n x^{n-1} and y''= \sum_{n=0}^{n-1}.
    Put those into the differential equation to get a "recursive equation" for the coefficents a_n. From y(0), a_0= 0. From y'(0)= 1, [tex]a_1= 1[tex]. Then determine a_2, a_3, and a_4.

    2) Recall that the first 6 terms of a McLaurin series for y is y(0)+ y'(0)x+ (y''(0)/2) x^2+ (y'''(0)/3!) x^3+ (y''''(0)4!)x^4+ (y'''''(0)/5!)x^5 ... . Then y(0)= 1, y'(0)= 1. For higher derivatives, evaluated at x= 0, solve the equation for y'': y''= (-xy+ y')/(1- x) so y''(0)= (y')/1= 1,

    y'''= (y'')'= ((-xy+ y')/(1- x))'= [(1-x)(-y- xy'+ y'')- (xy+ y')(-1))]/(1-x)^2

    so that y'''(0)= [1(-0- 0+ 1)- (0+ 1)(-1)]/1= 0, etc.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Newbie
    Joined
    Feb 2013
    From
    Hungary
    Posts
    24

    Re: Solving Diff Eq with initial conditions and first 6 coefficients...

    This second order linear ODE is homogeneous with respect to y, y' and y'' that is if F(x,y,y',y'') is a solution then F(x,ky,ky',ky'') is also a solution ( k \neq 0). In this case we may use the following transformation: y(x) = e^{\int u(x) \mathrm{d}x}. From the original differential equation we may conclude to (1-x)u'+(1-x)u^2-u+x=0 which is the general case of the Riccati-equation. We must find a particular solution to this first order d.e. If we can solve the Riccati differential equation, from y(x) = e^{\int u(x) \mathrm{d}x} we can determine y(x). However - according to Wolframalpha - the solution of the Riccati-equation involves exponential integral, which cannot be expressed with non-elementary functions. Therefore we cannot gain a closed formula for the differential equation, try a series method as HallsofIvy suggested.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. using initial conditions
    Posted in the Differential Equations Forum
    Replies: 2
    Last Post: March 17th 2011, 03:47 PM
  2. Initial conditions
    Posted in the Differential Equations Forum
    Replies: 2
    Last Post: June 9th 2010, 05:11 PM
  3. Does it matter when you use the initial conditions?
    Posted in the Differential Equations Forum
    Replies: 4
    Last Post: March 24th 2010, 12:52 PM
  4. Summation with initial conditions
    Posted in the Pre-Calculus Forum
    Replies: 1
    Last Post: September 23rd 2009, 02:05 PM
  5. PDE initial conditions
    Posted in the Calculus Forum
    Replies: 2
    Last Post: January 29th 2008, 08:42 PM

Search Tags


/mathhelpforum @mathhelpforum